Sex differences in Portuguese lonely hearts advertisements - Félix Neto (2005)
Advertisements from "Lonely Hearts" columns in the major daily Portuguese newspaper (Jornal de Noticias) were used to test hypotheses about the mate preferences of men and women. A total of 484 advertisements were coded for demographic descriptors and offers of and appeals for attractiveness, financial security, sincerity, expressiveness, and instrumentality, e.g., intelligence and ambition. Some results supported social exchange and evolutionary predictions: men Sought Younger women and offered Security; women Sought older men with status and resources. However, other results Challenged such predictions: attractiveness and expressiveness did not differ by sex.